2003
DOI: 10.1029/2002jd003270
|View full text |Cite
|
Sign up to set email alerts
|

Importance of dust particles in the free troposphere over the Taklamakan Desert: Electron microscopic experiments of particles collected with a balloonborne particle impactor at Dunhuang, China

Abstract: [1] Measurements of aerosol morphology and chemical elements were made in August 2002 at Dunhuang (40°00 0 N, 94°30 0 E), China, on the basis of direct sampling of free tropospheric aerosols with a balloonborne particle impactor, to understand nature of atmospheric particles over the desert areas in the Asian continent. Electron microscopic experiments of the particles directly showed that mineral (dust) particles were major constituents of coarse mode particles in the free troposphere over the Taklamakan dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
(51 reference statements)
8
40
0
Order By: Relevance
“…It is already suggested, on the basis of electron microscopic observation of the particles collected during intensive balloon-borne measurements, that most of the super micron particles in the atmosphere over the Taklamakan desert area are composed of Kosa particles (Iwasaka et al 2003b;Yamada et al 2005), and the present results strongly confirmed the suggestion as shown in Fig. 6.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is already suggested, on the basis of electron microscopic observation of the particles collected during intensive balloon-borne measurements, that most of the super micron particles in the atmosphere over the Taklamakan desert area are composed of Kosa particles (Iwasaka et al 2003b;Yamada et al 2005), and the present results strongly confirmed the suggestion as shown in Fig. 6.…”
Section: Discussionsupporting
confidence: 81%
“…7 was collected about 800 m above the ground (about 2 km above sea level). The particle shapes have many similar points which have been frequently observed with the electron microscope by many investigators (Iwasaka et al 1988;Okada and Kai 1995;Iwasaka et al 2003b). Several Kosa particles showed one (or more) fluorescence light spot on their surface, suggesting that materials containing DNA originated in biogenic aerosols are coating the Kosa particle surface.…”
Section: Particle Concentration and Mixture Of Kosa And Microorganismmentioning
confidence: 75%
“…Finally, the CALIPSO-based work of Liu et al (2008) also confirms our analysis and additionally shows that the Tarim Basin is dusty up to similar altitudes and in all months of the year except the winter months from December to February. The remote sensing measurements agree with balloon-borne measurements described by Iwasaka et al (2003), wherein dust was clearly the major component of the coarse mode, as detected by electron microscope analyses of particles collected by an impactor, up to 5 km over the eastern margin of the Tarim basin in August, 2002. Background summertime dust traced back to the Taklimakan desert was also detected by aircraft instrumentation and ground-based LIDAR over Japan .…”
Section: Seasonality Of Dust Emissionsupporting
confidence: 73%
“…In Aksu (northwestern Taklamakan), Kai et al (2008) measured depolarization ratios at 532 nm wavelength of 0.09 * -0.11 * in a lofted dust layer and 0.18 * -0.33 * in a near-ground dust layer. Iwasaka et al (2003) measured a depolarization ratio of 0.27 * at 532 nm wavelength in a lofted dust layer in Dunhuang (northern Taklamakan). Note that the values denoted with * are published as aerosol depolarization potentials and are converted to particle linear depolarization ratios (see Burton et al, 2014;Cairo et al, 1999;Gimmestad, 2008).…”
Section: Dust Particle Linear Depolarization Ratiomentioning
confidence: 99%